India means business how the elephant earned its stripes - Kaushik, Kshama V.; Dutta, Kaushik (New Delhi ; Oxford : Oxford University Press, 2012)
Looking at the many facets of the Indian business culture, this book traces the evolution of business in India from the pre-British Raj days to recent times.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Business enterprises -- India; Business enterprises -- India -- History; Business enterprises -- India -- Case studies